[Revisión del libro Behavioral psychotherapy. Basic principles and case Studies in an integrative clinical model, de H. Fensterheim y H. I. Glazer (Eds.)] - Pelechano, Vicente (Análisis y Modificación de Conducta, 1984)
Sin resumen